Fiscal expansions in the era of low real interest rates - Vaishali Garga (Federal Reserve Bank of Boston, 2020)
Low natural real interest rates limit the power of monetary policy to revive the economy due to the zero lower bound (ZLB) on the nominal interest rate. Fiscal stabilization via higher government debt is frequently recommended as a policy to raise the natural real interest rate. This paper builds a non-Ricardian framework to study the tradeoffs associated with a debtfinanced fiscal expansion and show that even in a low real interest rate environment, higher debt doesn't necessarily raise the real interest rate. The effect of the expansion is non-monotonic: Increasing debt raises the natural real interest rate at low levels of debt, while at high levels it perversely lowers the natural real interest rate. This threshold level of debt, beyond which the effect becomes perverse, is a function of the expected duration of the low interest rate state. In a calibrated 60-period quantitative life cycle model with aggregate uncertainty, if the low state is expected to last two years, this threshold level of debt is 250 percent of the GDP. The insights from this paper are directly applicable to a ZLB episode in a model with nominal frictions.
Keywords: E52; E62; E63; D84; 330; debt; fiscal policy; expectation; uncertainty